CREATING A SUSTAINABLE INTER-CITY ASEAN FOOTBALL LEAGUE, REGIONAL TELEVISION PROGRAMMING NETWORK, (CONTENT/IP INDUSTRY) SPORTS TOURISM AND TRAVEL INDUSTRY AND DEVELOPING PRINCIPLES FOR A LEGAL FRAMEWORK TO ACHIEVE ECONOMIC AND SOCIO-CULTURAL INTEGRATION - Han, Lim Peng (UI Scholars Hub, 2012)
China is poised to be the second largest economy in the world and investment will continue flowing into its growing affluent and gigantic domestic market. It is not surprising that the total inflow of Foreign Direct Investment (FDI) into ASEAN from the years 2007 to 2009 significantly shrunk from US74.3 billion to US39.6 billion. In 2010 ASEAN broadcasters paid a total of US182 million to enable 6 million subscribers to watch the English Premier League (EPL) games. ASEAN has the means to go on the offensive by creating its own Inter-City Football League consisting of 20 cities and 380 matches to be played over a ten-month period. The free-to-air live telecasts of the games can reach 139 million TV households and 89 million internet users. With an extensive audience, it is possible to earn US45 million of TV revenue, one per cent of the total TV expenditure of ASEAN countries. Moreover, many indigenous or foreign sponsors will be interested to sponsor the tournament, stadiums, teams, and players, making a league a sustainable project. Every team has to play 19 home and 19 away matches. A sustainable intra-ASEAN sports tourism and travel industry will emerge when each of the 20 team’s players, officials and supporters travel to the 19 cities for the away matches, fostering friendly competition and social integration. The stadium in each city no longer became “a white elephant” when the operators has to organised at least two matches a month. Traditional and contemporary song and dance shows organised before every match and telecast live can entertain and education a mass TV audience for cultural understanding and later, integration. The creation of an Inter-City ASEAN Football League would lead legal issues and challenges in the formulation of sports sponsorship contracts, regional broadcasting rights, management of stadiums and governance.